Erratum: Anker, A. (2012) “Revision of the western Atlantic members of the Alpheus armillatus H. Milne Edwards, 1837 species complex (Decapoda, Alpheidae), with description of seven new species”. Zootaxa, 3386, 1–109. - Anker, A. (Zootaxa, 2012)
(Erratum)